Preferência alimentar de adultos de Metriona elatior Klug (Coleoptera: Chrysomelidae, Cassidinae) por diferentes híbridos de Solanum melogena Linnaeus (Solanaceae) - Freitas Al Gazi, Ariel David; Gandolfo, Daniel; Pitelli, Robinson Antonio (Universidade Estadual de Maringa, 2008)
Feeding preference of adults of Metriona elatior Klug (Coleoptera: Chrysomelidae, Cassidinae) for different hybrids of Solanum melogena Linnaeus (Solanaceae). Metriona elatior Klug is a potential biocontrol agent for Solanum viarum Dunal (tropical soda apple), because larvae and adults feed on its leaves and this species shows a low dispersion rate. Specificity plays a major role in the feasibility of an organism as a biological control agent, especially in the inundative strategy. The feeding preference of M. elatior adults was evaluated to 14 eggplant (Solanum melogena Linnaeus) hybrids. Mass rearing was carried out under lab conditions, with the insect feeding directly on S. viarum leaves. The study started with dual and multiple choice tests in 24 and 48 hour feeding times, by offering leaf disks in Petri dish conditions. Survival and leaf consumption analysis were performed in newly adults in tropical soda apple and eggplant leaves kept turgid by immersing the petioles in water. The leaf area was measured before and after four days of insect exposure. M. elatior showed higher feeding preference, survival and consumption of the weed species, especially in comparison with the hybrid Ryoma. The highest feeding preference among the eggplant hybrids was observed in 'Minikuro Kowishiki'.
Feeding preference of adults of Metriona elatior Klug (Coleoptera: Chrysomelidae, Cassidinae) for different hybrids of Solanum melogena Linnaeus (Solanaceae).